Daily physical activity, coffee and energy drink consumption, and sleep patterns among Chinese elite professional esports athletes: a case study of Zhejiang Regans Gaming - Pang, Zhihui; Su, Lide; Zhang, Yang (Frontiers in Public Health, 2025)
PurposeEsports is increasingly recognized as both a legitimate sport and profession. However, evidence on the health behaviors of esports athletes remains limited. Due to the nature of their activity, these athletes face occupational health risks associated with prolonged sedentary behavior, sleep deprivation, and excessive energy drink consumption. This study aimed to document the health behaviors of professional esports athletes.MethodsThis case study sampled athletes from Zhejiang Regans Gaming, who are full-time professionals competing at the elite level. Data were collected over three training days, with moderate-to-vigorous physical activity and sleep patterns monitored using the Apple Watch Series 9.ResultsAthletes trained for an average of 13 h daily in a seated position, engaging in only 35.6 ± 0.9 min of moderate-to-vigorous physical activity. The extended training hours led to delayed sleep schedules, with a typical bedtime of 3:05 a.m. Sleep quality was poor, with athletes averaging 45.2 ± 13.0 min awake in bed, 392.8 ± 13.9 min of total sleep, and a sleep efficiency of 89.7 ± 3.0%. Likely due to sleep deprivation, athletes consumed an average of 2 cups of coffee and 2.5 ± 0.4 bottles of energy drinks daily.ConclusionThis study offers firsthand evidence of the concerning health behaviors among Chinese elite professional esports athletes. Physical activity levels and sleep quality are notably poor, while energy drink consumption is prevalent. Team managers should monitor sleep quality and energy drink consumption, while governing bodies must recognize the long-term risks of excessive sedentary behavior in esports.